PEMERIKSAAN PROTEIN URINE DENGAN MENGGUNAKAN PERASAN BELIMBING WULUH (Averrhoa bilimbi L) DAN REAGENSIA ASAM ASETAT 6% - Yusrita, Eli; Agustin, Feby (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Protein determination is a routine chemical examination of urine that most clearly indicates the presence of kidney disease. One of the reagents used to examine urine protein is a 6% acetic acid solution. Starfruit (Averrhoa bilimbi L) contains alphatic acid (acetic acid and citric acid). Starfruit has similar properties to acetic acid with a pH of 2.0. This examination technique works by adding acid and heating the protein in the urine. The aim of this research was to determine the effectiveness of star fruit water (Averrhoa bilimbi L) as an alternative reagent for urine protein examination. This research is experimental in nature and the research results obtained from fifteen samples taken at the Harapan Raya Community Health Center and found to be positive. From the research that has been carried out, it was found that starfruit (Averrhoa bilimbi L) is effective as an alternative reagent for urine protein at concentrations of 3%, 5% showing the same reaction results as the reaction results using 6% acetic acid. The conclusion of this research is that Starfruit (Averrhoa bilimbi L) at a concentration of 1% is not effective as an alternative reagent for urine protein, while at concentrations of 3%, 5% shows it is effective as an alternative reagent for urine protein.Keywords: Starfruit (Averrhoa bilimbi L), Urine protein, Acetic acid 6%